Legalitas Penggunaan Konsep Cyber Notary Dalam Prakteknya Di Indonesia - Fauzan Aziman Alhamidy; FX Arsin Lukman (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
As technology develops in Indonesia, electronic signatures are often used as evidence in entering into agreements or transactions in Indonesia. Technological developments from time to time have experienced these changes occur in various aspects of human life. Advances in technology have increased innovation to facilitate mobility in life. Legal practitioners, especially notaries, take advantage of technological developments to sign a deed. With the development of this technology, the concept of cyber notary was created, namely a concept that utilizes technological advances in carrying out the duties and authority of a notary. In the Notary Office Law No. 2 of 2014, notaries are permitted to certify through electronic documents. Thus the opportunity to make the Cyber Notary concept no longer collide because there is already a law that regulates it. This writing uses the Normative Juridical method, namely library research that describes secondary data, namely primary legal materials in the form of laws and regulations secondary legal materials such as books and scientific papers related to research topics. The scope of this research is the legality of using the cyber notary concept in Indonesia. This study aims to discuss, investigate, and present issues related to the legality of the Cyber Notary concept in Indonesia.